Risk in coopetition between logistics enterprises - Frąś, Józef; Frąś, Tomasz; Domański, Roman (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: Coopetition, as a way to increase the operational efficiency of business operations, is an attractive but high-risk strategy. The aim of the study was to demonstrate that logistics enterprises undertaking competitive cooperation related to the supply chain in the area of supply and production logistics, while increasing their competitive advantage, are at the same time exposed to a greater risk of losing strategic resources. Methodology: Risk in this context means that despite the effective management of logistics processes within the framework of coopetition between enterprises, there may be circumstances related to the risk of cooperation which will make it difficult to achieve results in the area of enterprise logistics in coopetition relations. Regarding the acquisition of information, qualitative research was used, based on the knowledge of experts and employees involved in logistics processes as part of coopetition between the surveyed logistics enterprises, especially in the area of supply and production processes. Results: This article presents the results of research into the risks in the area of logistics processes for selected 49 companies belonging to the TSL (transport, shipping, logistics) sector out of a research group of 223 companies belonging to various sectors, including information technology, transport, production, finance, cooperating within competitive ties. The outcome of the undertaken research is the identification of significant threats related to competitive cooperation between enterprises, which has a significant impact on logistics activities and processes which ensure the assumed effects of this cooperation. The study allowed to determine the risks that exist in the competitive cooperation processes in the surveyed enterprises. Implications and recommendations: The conducted research related to the identification of risks of competitive cooperation has a practical dimension, because by identifying them we have a picture of threats to competitive cooperation. Secondly, before making a decision on competitive cooperation, this risk should be estimated and the right decision should be made. Originality/value: The article provides valuable guidelines useful for business practice in the form of a classification of the sources of risk occurring in the process of coopetitioning between enterprises at different stages of cooperation, considered in different cross-sections (object of exchange, number of entities, degree of formalisation of cooperation, intensity of relations). These findings should help avoid problematic situations in the coopetitive relation.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 110-125
Keywords: risk; coopetition; logistics processes; risk factors; risk measurement; risk level